Graphene‐Based Actuator with Integrated‐Sensing Function. (14th November 2018) - Chen, Luzhuo; Weng, Mingcen; Zhou, Peidi; Huang, Feng; Liu, Changhong; Fan, Shoushan; Zhang, Wei
Abstract: Flexible actuators have important applications in artificial muscles, robotics, optical devices, and so on. However, most of the conventional actuators have only actuation function, lacking in real‐time sensing signal feedbacks. Here, to break the limitation and add functionality in conventional actuators, a graphene‐based actuator with integrated‐sensing function is reported, which avoids the dependence on image post‐processing for actuation detection and realizes real‐time measurement of the shape‐deformation amplitudes of the actuator. The actuator is able to show a large bending actuation (curvature of 1.1 cm −1 ) based on a dual‐mode actuation mechanism when it is driven by near infrared light. Meanwhile, the relative resistance change of the actuator is −17.5%. The sensing function is attributed to piezoresistivity and thermoresistivity of the reduced graphene oxide and paper composite. This actuator can be used as a strain sensor to monitor human motions. A smart gripper based on the actuators demonstrates perfect integration of the actuating and sensing functions, which can not only grasp and release an object, but also sense every actuation state of the actuator. The developed integrated‐sensing actuator is hopeful to open new application fields in soft robotics, artificial muscles, flexible wearable devices, and other integrated‐multifunctional devices. Abstract : A graphene‐based actuator with integrated‐sensing function is developed. It realizes real‐time measurements of the shape deformation of the actuator. A smart gripper based on the actuator demonstrates perfect integration of actuating and sensing functions. It can not only grasp and release an object, but also sense every actuation state of the actuator.